RUSSIAN FOREIGN TRADE: GRAVITY APPROACH - N. Chernov (Вестник университета)
The methodology of gravity model and specialties of its use in relation to Russian foreign trade are presented. The results of the calculation of Russian foreign trade gravity model with its explanation both for total trade flows and trade flows excluding mineral fuel, oil and oil products are given. The high accuracy and the possibility of using this methodology for researching of Russian foreign trade process and trade affecting factors including access to the sea are confirmed.